Chromosomal location of structural genes encoding murine immunoglobulin lambda light chains. Genetics of murine lambda light chains (The Rockefeller University Press, 1981)
To determine the chromosomal localization of murine lambda light (L) chain structural genes, DNA from a panel of 11 mouse x hamster somatic cell hybrids was scored for the presence of sequences homologous to cloned lambda DNA probe molecules. Six of the hybrids had detectable lambda I and lambda II gene sequences. In all six, the full complement of murine sequences was present, and in its germline configuration. The remaining hybrids lacked any detectable murine lambda L chain gene sequences. The only mouse chromosome present in all of the positive hybrids and absent from the negative ones was number 16, allowing the assignment of lambda L chain structural genes to this chromosome. Together with the previous assignments of the kappa L chain genes to chromosome 6 and heavy chain genes to chromosome 12, this finding completes the mapping of Ig structural genes in the mouse at the chromosomal level.